Highway concessions and road safety:Evidence from Brazil. (December 2021) - Alves, Pedro Jorge; Emanuel, Lucas; Pereira, Rafael H.M.
Abstract: Reducing road fatalities is a key policy goal in several countries and there is a vast literature on what factors affect road safety performance. Nonetheless, there is limited evidence on whether highway concessions and Public Private Partnerships (PPP) can bring road safety benefits, despite the growing number of countries adopting this type of policy to finance and manage road infrastructure. In this paper, we use a difference-in-differences approach to examine the causal effect of highway concessions on road safety outcomes using daily data from Brazilian Federal highways over 11 years between 2007 and 2017. We exploit the transition from public to private management in some but not all Brazilian states to provide both within- and between-states comparison. We find that concessions promote a small but significant reduction in the number and fatality of road crashes as well as and the number of people and vehicles involved in crashes. Between 2007 and 2017, procured roads had on average 16 fewer deaths then publicly managed highways for every 1000 crashes each year. These road safety benefits only become statistically significant a few years after a concession implementation, but they are marginally larger for every additional year of concession. Finally, our results suggest that including safety-based incentives in concession contracts can substantially improve road safety performance. The findings of the paper have important implications for the social and economic evaluation of road concessions and for road infrastructure policy more broadly.